Pengaruh Kepercayaan dan Kepuasan Konsumen Terhadap Loyalitas Konsumen Pengguna Sim Card Telkomsel: (Studi Kasus Pada SMA Negeri 1 Selat) - Witari, Ni Luh Ayu Desi; Suartina, I Wayan (WidyaAmrita: Jurnal Manajemen, Kewirausahaan dan Pariwisata, 2023)
The purpose of this study is to find out the influence of trust, and consumer satisfaction on the consumer loyalty of Telkomsel Sim Card users (Case Study at SMA Negeri 1 Selat) partially and simultaneously. In this study the data collection methods used were observations, interviews, documentation and questionnaires. The population in this study was 75 students of Sma Negeri 1 Selat class of 2020 who used The Tekomsel Sim Card. The sample used in this study was 75 respondents, using saturated sampling methods. The data analysis technique used in this study is Multiple Linear Regeresi Analysis. From the results of the study obtained consumer trust and satisfaction has a positive and significant effect simultaneously on consumer loyalty. This is evidenced by the value of Fhicount of 134,942 compared to Ftabel indigo of 3.12. Trust has a positive and significantly significant effect on consumer loyalty. This is evidenced by the thitung value of 2,647 compared to the ttabel value of 1,993. Consumer satisfaction has a positive and significantly partial effect on consumer loyalty. This is evidenced by the thitung value of 3,680 compared to the ttabel value of 1,993. Researchers should then be able to examine and examine more in other factors not studied in this study that can affect consumer loyalty.